Prevalence of pulp calcifications in posterior teeth assessed by cone-beam computed tomography in patients treated at a radiology center - Lavado García, Mayra Isaura (2026)
Objective: To determine the prevalence of pulp calcifications in permanent posterior teeth using cone-beam computed tomography (CBCT) at a radiology center in Tacna during the 2020–2023 period. Materials and methods: A non-experimental, retrospective, cross-sectional study was conducted. Training was provided by an oral and maxillofacial radiology specialist, with whom 15 CBCT scans were reviewed using standardized consensus criteria. 163 CBCT scans (FOV: 16 × 10 mm), comprising 2,060 dental units, were randomly selected and analyzed. Image analysis was performed using NNT Viewer software, evaluating each tooth in sagittal, axial, and coronal planes. The chi-square statistical test was used to assess the association between tooth condition and the presence of pulp calcifications, as well as between patient age and the occurrence of these calcifications. Results: Of the 163 CBCT scans evaluated, 26.2% of the 2,060 dental units presented pulp calcifications. Prevalence was higher in females and in the 17–36-year age group, although no statistically significant differences were observed. The category with the highest prevalence was “intact teeth.” A significant association was found between tooth condition and the presence of pulp calcifications. Conclusions: Pulp calcifications are a relatively common condition in permanent posterior teeth. Their presence is more closely associated with the structural condition of the tooth rather than with factors such as age or sex.